Comparison of two distinct house ball communities involved in an HIV prevention study: Baseline data from the POSSE project. Issue 4 (2nd October 2019) - Hosek, Sybil; Castillo, Marne; Hotton, Anna; Balthazar, Christopher; Gwiazdowski, Bevin; Laboy, Richard; Davis, Kortez; Lemos, Diana; Harper, Gary W.; Bell, Margo
Abstract: For many Black/African American gay, bisexual, and other young men who have sex with men (B-GBMSM), the House/Ball Community (HBC) offers a social network where they can be free to express diverse sexual and gender identities, but HIV prevalence and stigma are high. The POSSE project is an effectiveness-implementation trial of a popular opinion leader intervention designed to address HIV prevention in the Chicago and Philadelphia HBCs. In June 2016 baseline behavioral data were collected along with HIV, gonorrhea and Chlamydia testing. Eligible participants were sexually-active YMSM or transgender women (TGW), between the ages of 15 and 24, who self-identified as Black. One-third participants (32.5%) met or exceeded the clinical cutoff for depressive symptoms. Approximately 18% of the participants across both cities reported that they were HIV-positive. Overall, the baseline data establishes the need for HIV and STI prevention interventions across both cities, as well as interventions to address other co-occurring epidemics.